Effect of potassium fertilization and roselle extract foliar application on growth and yield of two turnip (Brassica rapa L.) cultivars - Marleen Karim Rasool (Journal of Kerbala for Agricultural Sciences, 2025)
A field experiment was conducted in the field of the Department of Horticulture and Landscape Engineering, College of Agriculture, University of Kerbala, in Al-Husseiniya District, Kerbala Governorate, during the autumn season 2024-2025, with the aim of studying the effect of adding potassium fertilizer and spraying roselle extract on the growth and yield of two turnip cultivars. The experiment was carried out according to a randomized complete block design (RCBD) with three replicates according to the factorial arrangement of three replications. The first factor included seven fertilization treatments (control potassium 100 kg K₂O ha-1, potassium 200 kg K₂O ha-1, potassium 100 kg K₂O ha-1 + spraying roselle extract at a concentration of 4 mg L-1, potassium 100 kg K₂O ha-1 + spraying roselle extract at a concentration at 8 mg L-1, potassium 200 kg K₂O ha-1 + spraying roselle extract at a concentration of 4 mg L-1, and potassium 200 kg K₂O ha-1 + spraying roselle extract at a concentration at 8 mg L-1), and symbolized as T1, T2, T3, T4, T5, T6 and T7 respectively. While the second factor included two cultivars of turnip plants, a local cultivar (A) and an Iranian cultivar (B).